Opium trade and the spread of HIV in the Golden Crescent - Farooq, Syeda Ayesha; Rasooly, Mohammad Hafiz; Abidi, Syed Hani; Modjarrad, Kayvon; Ali, Syed (Harm Reduction Journal, 2017)
The Golden Crescent region of South Asia—comprising Afghanistan, Iran, and Pakistan—is a principal global site for opium production and distribution. Over the past few decades, war, terrorism, and a shifting political landscape have facilitated an active heroin trade throughout the region. Protracted conflict has exacerbated already dire socio-economic conditions and political strife within the region and contributed to a consequent rise in opiate trafficking and addiction among the region’s inhabitants. The worsening epidemic of injection drug use has paralleled the rising incidence of HIV and other blood-borne infections in the region and drawn attention to the broader implications of the growing opiate trade in the Golden Crescent. The first step in addressing drug use is to recognize that it is not a character flaw but a form of mental illness, hence warranting humane treatment of drug users. It is also recommended that the governments of the Golden Crescent countries encourage substitution of opium with licit crops and raise awareness among the general public about the perils of opium use.
Keywords: HIV; Opium; Golden crescent; Afghanistan; Iran; Pakistan